How Patients Choose a Laryngologist: A Pilot Stated Preference Study - Victoria Fischman; Eve Wittenberg MPP, PhD; Sungjin A. Song MD; Molly N. Huston MD; Ramon A. Franco MD; Phillip C. Song MD; Matthew R. Naunheim MD, MBA (OTO Open, 2021)
Objective Patients consider many factors when deciding how to receive medical care. This study used best-worst scaling (BWS), a technique novel to otolaryngology, to quantitatively examine preferences among patients choosing a laryngologist. Our objective was to quantify in a pilot cohort the relative importance patients place on a variety of attributes when seeking a laryngologist. Study Design BWS survey. Setting Academic voice clinic. Methods New patients were recruited to take a computerized BWS survey developed using attributes derived from patient input, expert opinion, and literature review. Attributes were grouped into 4 categories: physician reputation, physician qualifications, hospital-related factors, and other nonclinical factors. Responses were analyzed using multinomial logit regression to determine importance scores and associations with other variables. Results Eighty-seven of 93 patients recruited participated (93.5% response rate). Physician qualifications were the most important attributes to patients, with specialty laryngology training receiving the highest importance score (20.8; 95% CI, 20.2 to 21.5; P < .0001). Recommendations from referring physicians (15.6; 95% CI, 14.3 to 16.9) and use of cutting-edge technology (11.9; 95% CI, 10.7 to 13.1) were the second and third most important, respectively. Least important were nonclinical factors, including wait time to get an appointment (4.3; 95% CI, 2.8 to 5.8) and convenience of office location (1.5; 95% CI, 0.9 to 2.1). Just over half of patients (51.2%) reported willingness to wait 4 weeks for an appointment with a laryngologist. Older patients were less concerned with convenience-related factors. Conclusion Nonclinical factors were less important to patients than clinical factors, and laryngology-specific training was paramount. Stated preference methodologies can elucidate underlying preferences and help providers make care more patient centered.